(untitled) (Research, Society and Development, 2021)
The rational consumption of residential water is one of the main issues to be addressed in today since it represents an important part of the consumption of water resources in our society. Aware of this, an algorithm was developed to aid in the optimization of the use of hydraulic devices in residential environments, testing this proposal in a generic residential environment. In order to reach this objective, market surveys and technical reference were made to collect data from the hydraulic devices and later the genetic algorithm technique was used for optimization processing. As a result, we found a set of optimal scenarios for the use of the devices, ensuring greater water savings at the lowest cost. It was concluded that the work proposes an optimization routine that can have satisfactory applicability for decision making in the optimization of the use of residential hydraulic devices.